1992
DOI: 10.1007/bf01752970
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial pneumonia: Epidemiology and infection control

Abstract: Elderly, debilitated, or critically ill patients are at high risk for hospital acquired or nosocomial respiratory tract infection. Gram-negative bacilli, Staphyloccoccus aureus, and anaerobes colonizing the oropharynx are the most frequent etiologic agents. Colonization of the oropharynx may be related to the patient's age, underlying disease, nutritional status, prior exposure to antibiotics, supine position, and gastric colonization. Nosocomial pathogens may also be acquired from the hands of hospital person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 61 publications
0
17
0
4
Order By: Relevance
“…In a series of international surveillance studies, pneumonia accounted for 14-20% of all nosocomial infections and was repeatedly found to be the second most frequent type of hospital-acquired infection after urinary tract infection. The US National Nosocomial Infections Surveillance System (NISS) identified six to ten episodes of nosocomial pneumonia (NP) for every 1,000 patients admitted to hospital [1][2][3][4][5][6]. The highest rates of NP occur in intensive care units (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of international surveillance studies, pneumonia accounted for 14-20% of all nosocomial infections and was repeatedly found to be the second most frequent type of hospital-acquired infection after urinary tract infection. The US National Nosocomial Infections Surveillance System (NISS) identified six to ten episodes of nosocomial pneumonia (NP) for every 1,000 patients admitted to hospital [1][2][3][4][5][6]. The highest rates of NP occur in intensive care units (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…VAP is defined as having either an early- or a late-onset according to whether it begins before or after the first 5 to 7 days of hospitalization [4]. During early-onset ventilator-associated pneumonia (EOVAP), the normal bacterial flora consists of Haemophilus influenzae , Streptococcus pneumoniae , methicillin-sensitive Staphylococcus aureus , Moraxella catarrhalis and non multiresistant Escherichia coli [5], [6]. The bacteria isolated may vary due to antibiotic treatment, recent hospitalization and ICU ecology [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…GNB, such as Pseudomonas aeruginosa, Klebsiella pneumoniae and Enterobacter spp. are putative pathogens and can cause infections such as pneumonia [2]. It has been shown that the incidence of infection with GNB rises in institutionalised patients and frail elderly subjects [3].…”
Section: Introductionmentioning
confidence: 99%